2010
DOI: 10.1016/j.micres.2009.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Self-resistance mechanism in Streptomyces peucetius: Overexpression of drrA, drrB and drrC for doxorubicin enhancement

Abstract: The resistance genes drrABC from Streptomyces peucetius ATCC 27952 were cloned into the pIBR25 expression vector under a strong ermE* promoter to enhance doxorubicin (DXR) production. The recombinant expression plasmids, pDrrAB25, pDrrC25 and pDrrABC25, were constructed to overexpress drrAB, drrC and drrABC, respectively, in S. peucetius ATCC 27952. The recombinant strains produced more DXR than the parental strain: a 2.2-fold increase with pDrrAB25, a 5.1-fold increase with pDrrC25, and a 2.4-fold increase wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 16 publications
2
42
0
Order By: Relevance
“…Matilla and colleagues (35) found that expression of PP2669 was strongly induced when KT2440 was present in the rhizosphere of plants, an environment where oxidative stress induced by antimicrobial secondary metabolites is relevant (7,64). PP2668 and PP2667 exhibited conserved sequences with respect to the DrrAB efflux system of Streptomyces that confers self-protection to producer strains against daunorubicin and doxorubicin, two anthracycline-type aromatic compounds (27,30,34). Thus, in KT2440, the efflux system consisting of PP2669/PP2668 and PP2667 may be involved in the direct efflux of chloramphenicol.…”
Section: Discussionmentioning
confidence: 99%
“…Matilla and colleagues (35) found that expression of PP2669 was strongly induced when KT2440 was present in the rhizosphere of plants, an environment where oxidative stress induced by antimicrobial secondary metabolites is relevant (7,64). PP2668 and PP2667 exhibited conserved sequences with respect to the DrrAB efflux system of Streptomyces that confers self-protection to producer strains against daunorubicin and doxorubicin, two anthracycline-type aromatic compounds (27,30,34). Thus, in KT2440, the efflux system consisting of PP2669/PP2668 and PP2667 may be involved in the direct efflux of chloramphenicol.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, various self-protection mechanisms have been reported [15], and by enhancing these selfprotection mechanisms, the production of many antibiotics has been increased in various microorganisms. For example, Malla et al [14] overexpressed the resistance genes drrA, drrB and drrC in Streptomyces peucetius ATCC 27952, such that the recombinant strains produced more doxorubicin (DXR) than the parental strain. Indeed, there was a 2.2-fold increase in DXR in the drrAB mutant, a 5.1-fold increase in the drrC mutant and a 2.4-fold increase in the drrABC mutant.…”
Section: Discussionmentioning
confidence: 99%
“…After 6 days of incubation, mature spores were found on the surface of the SRI colony, but the SRI-B80 spores were malformed and immature. The onset of morphological differentiation generally coincides with the production of secondary metabolites and resistance genes are often co-regulated with these metabolites [14]. Indeed, spore formation is very closely related with the expression of resistance genes.…”
Section: Screening Of the High-productivity Mutantsmentioning
confidence: 99%
“…producing daunorubicin and doxyrubicin [62] or netropsin (23) [63]. Similarly, intracellular accumulation can also be reduced through mutations in proteins involved…”
Section: Resistancementioning
confidence: 99%